Entrepreneurship : networking for some Chinese entrepreneurs - Dachlan, Gery (2014)
The dynamic nature of entrepreneurship has been attracting a great deal of attention recently. The reason lies in the fact that entrepreneurs are driven by many factors towards their road to success. The aim of this project is to isolate the effects of networking and observe its significance for local Chinese entrepreneurs. As earlier studies had mainly focused on the research of psychological characteristics of entrepreneurs, this study aims to help create awareness of the networking phenomenon among entrepreneurs for researchers and entrepreneurs alike.